2015
DOI: 10.2527/jas.2014-7371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding peroxidized dried distillers grains with solubles to sows and progeny on growth performance and metabolic oxidative status of nursery pigs1

Abstract: This experiment evaluated the effects of including peroxidized corn dried distillers grains with solubles (DDGS) in diets for sows and nursery pigs on growth performance, vitamin E (VE), and Se status, and the incidence of mulberry heart disease (MHD) of nursery pigs. Sows (n = 12) were fed corn-soybean meal diets (C-SBM) or C-SBM diets with DDGS (40% and 20% in gestation and lactation, respectively) for 3 parities. In the third parity, 108 weaned pigs (BW = 6.6 ± 0.36 kg) were blocked by BW within litter, ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…These results suggest that antioxidant capacity and lipid soluble phytochemicals may vary substantially among DDGS sources. Furthermore, the knowledge of the antioxidant capacity of feed ingredients may be important for minimizing the risk of negative nutritional and physiological effects associated with metabolic oxidative stress ( Hanson et al, 2015b , Kerr et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that antioxidant capacity and lipid soluble phytochemicals may vary substantially among DDGS sources. Furthermore, the knowledge of the antioxidant capacity of feed ingredients may be important for minimizing the risk of negative nutritional and physiological effects associated with metabolic oxidative stress ( Hanson et al, 2015b , Kerr et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E has been reported to decrease in animals fed peroxidized lipids (Luci et al, 2007;Ringseis et al, 2007;Boler et al, 2012;Hanson et al, 2016), and this is consistent with our findings. In contrast, feeding oxidized DDGS increased serum vitamin E concentrations in pigs (Hanson et al, 2015). It has been demonstrated that vitamin E concentrations decrease in complete diets ensuing addition of peroxidized oils (Luci et al, 2007;Ringseis et al, 2007;Hanson et al, 2016).…”
mentioning
confidence: 99%
“…This degree requires at least the increase correspondingly production the consumer goods too, in particularly, the ecological pure and natural materials. In limited allocated for agriculture area conditions and continuing area reduction because of construction the new residential and indusdtrial areas there is increasing possibility the production volume only through acceleration the growth of agricultural culteres [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%